1999
DOI: 10.1017/s1355838299981967
|View full text |Cite
|
Sign up to set email alerts
|

The splicing factors 9G8 and SRp20 transactivate splicing through different and specific enhancers

Abstract: The activity of the SR protein family of splicing factors in constitutive or alternative splicing requires direct interactions with the pre-mRNA substrate. Thus it is important to define the high affinity targets of the various SR species and to evaluate their ability to discriminate between defined RNA targets. We have analyzed the binding specificity of the 30-kDa SR protein 9G8, which contains a zinc knuckle in addition to the RNA binding domain (RBD). Using a SELEX approach, we demonstrate that 9G8 selects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
216
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(239 citation statements)
references
References 71 publications
21
216
1
1
Order By: Relevance
“…Furthermore, p25 cross-links decreased in intensity upon addition of cold competitor. Taken together, these results confirm previous observations that SRp20 can bind to RNA independent of splicing (Cavaloc et al 1999;Schaal and Maniatis 1999), but this binding is relatively weak. However, like REF/Aly, its association with the 5Ј exon is apparently stabilized upon exon ligation, as evidenced by stronger p25 cross-linking to spliced RNAs (Fig.…”
Section: Enhanced 5ј Exon Association Of Ref/aly and Srp20 Upon Exon supporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, p25 cross-links decreased in intensity upon addition of cold competitor. Taken together, these results confirm previous observations that SRp20 can bind to RNA independent of splicing (Cavaloc et al 1999;Schaal and Maniatis 1999), but this binding is relatively weak. However, like REF/Aly, its association with the 5Ј exon is apparently stabilized upon exon ligation, as evidenced by stronger p25 cross-linking to spliced RNAs (Fig.…”
Section: Enhanced 5ј Exon Association Of Ref/aly and Srp20 Upon Exon supporting
confidence: 91%
“…3A), cross-linked p25 was detectable (although weakly) even at 0 min, prior to spliceosome assembly. Consistent with the known ability of SRp20 to interact with RNAs independent of splicing (Cavaloc et al 1999;Schaal and Maniatis 1999), p25 cross-links were also weakly detectable in the PIP.B+10 intronless control mRNA fractionations (Fig. 3D, left).…”
Section: Identification Of Two Cross-linked Species As Srp20 and Ref/alysupporting
confidence: 77%
“…Many different sequence elements have been described over the past several years that can serve as splicing enhancers+ A majority of these act through the interaction of SR proteins with the pre-mRNA+ Whether they were identified through SR protein binding assays or via functional selection of splicing activity, it is clear that the initial generalization of splicing enhancers as purinerich sequences did not reflect the true complexity of active enhancer elements (for a recent compilation of selected sequences, see Tacke & Manley, 1999)+ The sequence SGACS that we have identified as an active trans-splicing enhancer in homologous A. lumbricoides extracts has also been identified previously (Tacke & Manley, 1995;Shi et al+, 1997;Liu et al+, 1998;Bourgeois et al+, 1999;Schaal & Maniatis, 1999b)+ It has been isolated in single clones deduced through binding assays with SF2/ASF, splicing assays in S100 extracts supplemented with SF2/ASF, and also in open-ended screens for active splicing enhancers+ In only one of these reports did the sequence emerge enough times to be included in the consensus (Schaal & Maniatis, 1999b)+ The first of these sets of experiments examined sequences that could interact with histidine-tagged SF2/ASF ⌬RS through retention on Ni 2ϩ agarose (Tacke & Manley, 1995)+ Here the consensus sequence (AGGACAGAGC) is close to SGACS and in fact 11 out of 36 sequences in this category contain perfect SGACS motifs+ Functional selection, driven by the presence of exogenous SF2/ASF has also yielded a similar consensus (SRSASGA) and as in the previous example, a subset (5 out of 28) of the members of this class contain SGACS elements (Liu et al+, 1998)+ These two reports both implicate SF2/ASF as a candidate for interaction with the sequence SGACS+ Two other sets of experiments that noted SGACS elements reported that they responded to SC35 (Schaal & Maniatis, 1999b) or served as a component of an element that interacted strongly with Drosophila melanogaster B52 (SRp55; Shi et al+, 1997)+ Finally, a natural example of an element containing an SGACS motif has been implicated in bidirectional activation of both an upstream 39 splice site and a downstream 59 splice site in adenovirus E1A pre-mRNA (Bourgeois et al+, 1999)+ Mediation of downstream 59 splice site activation was shown to correlate with binding of the SR protein 9G8+ In our site-specific crosslinking experiments, we observe crosslinks to an SR protein(s) that migrates at ;30 kDa, the same size as SF2/ASF, SC35, and 9G8+…”
Section: Comparison Of Selected Enhancers That Promote Trans-splicingmentioning
confidence: 65%
“…The duration of incubation at 30°C was for 2 h and 30 min. For SR protein assays, 150 or 300 ng of purified 9G8, ASF/SF2, SC35, or SRp40 recombinant protein were used, prepared as described previously (44). The degree of purity of these proteins was verified by electrophoresis followed by argentic staining and Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%